Adolescent male orphans affected by HIV and AIDS, poverty and fatherlessness: A story of marginalisation? - Meyer, Juanita (HTS teologiese studies, 2013)
This article explores the experiences of fatherless adolescent males affected by HIV, AIDS and poverty, in order to investigate how these experiences influence the creation of their alternative, future narratives and if these experiences result in narratives that speak of marginalisation or instead, will speak of survival. Research methods from the qualitative case study research design are employed. The theoretical point of departure is a postfoundational practical theology and narrative therapy. The specific focus is on issues of marginalisation and to listen to the narratives within their contexts. The article explores and deconstructs the dominant discourses engrained within the larger socio-economic and cultural context and questions whether these narratives should be viewed as a story of marginalisation. The article concludes that it is not a story of marginalisation, but rather a story of survival, a story of hope.